Production, characterization and migration of melt-blended and layer-deposited polyethylene silver nanocomposite as antibacterial food packaging - Jokar, Maryam (2012)
Antimicrobial packaging, a promising form of active packaging, is an innovative concept which has been the subject of substantial research for only the last two decades. The aim of this study was to incorporate silver nanoparticles into polyethylene films and to investigate physical and antimicrobial properties and silver ion migration of polyethylene nanocomposite. Silver nanoparticles with a uniform size of 5.5±1.1 nm were prepared by chemical reduction using polyethylene glycol (PEG) as stabilizer as well as reducing agent of silver nitrate. Silver colloid dispersion showed typical visible spectra band at 447 nm and also significant (p<0.05) antimicrobial effects on Escherichia coli, Staphylococcus aureus by agar plate test. Low density polyethylene (LDPE) was used as polymer matrix. LDPEsilver nanocomposites produced by two methods of (i) melt blending and (ii) layer by layer (LBL) self assembly deposition. In melt blending, silver nanoparticles at five concentration levels were added into low density polyethylene (LDPE) pellets by melt blending and subsequent hot pressing at 140 °C. Melt blended LDPE silver nanocomposites were characterized by atomic force microscopy (AFM) and X-ray diffraction (XRD) for morphology and size feature and then mechanical, thermal and barrier properties were investigated. Silver nanoparticles did not influence mechanical and thermal properties of melt blended LDPE silver nanocomposite significantly (p>0.05). Melt blended LDPEsilver nanocomposite showed clear zone and significant effect on the growth kinetic parameters of S. aureus andE. coli. In LBL deposition method, nanocomposite films were prepared by sequential dipping of a LDPE film in either anionic silver colloid dispersion or cationic chitosan with the thickness of 2, 4, 8, 12, 16 and 20 layers. LBL deposited silver nanocomposite films were characterized by electron microscopy and then mechanical, thermal and barrier properties of LBL deposited silver nanocomposites were also investigated. Silver nanoparticles increased crystallinity of LDPE films which was determined by differential scanning calorimeter (DSC) and resulted in improving barrier properties. Chitosan coating increased mechanical elongation strength significantly (p<0.05). Antimicrobial efficiency of LBL deposited silver nanocomposites was considerably higher than melt blended ones because silver nanoparticles are trapped in melt blended polymer composites but could release easier in LBL coated nanocomposites. It can be concluded that LBL deposition is preferable than the melt blending processing to produce LDPE silver nanocomposite due to more antimicrobial activity and improved mechanical and barrier properties against water vapor and oxygen. The silver ion released from either melt blended or LBL deposited silver nanocomposites into EU standard food stimulants (deionized water, 3% acetic acid and 10% ethanol alcohol) and apple juice during 30 days at 4 and 40 °C was determined by atomic absorption spectroscopy(AAS) and analyzed using factorial and response surface designs. Production method, silver concentration, temperature, time and contact media showed significant effect (p<0.05) on silver ion migration,respectively. The quantity of silver ion migration from nanocomposites into food stimulants and apple juice was less than allowable concentration (10 ppm) at all cases over 30 days. LBL deposition method, more silver concentration in the polymer, higher temperature and acidic property of contact liquid promote more silver ion release from nanocomposite films. Migration of silver ions from nanocomposites obeyed first order diffusion kinetic.